PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI KULA KOPI - Misniasari, Nia; Fahleti, Widya; Dewi, Septira (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2025)
The study entitled The Influence of Service Quality and Promotion on Purchasing Decisions at Kula Kopi aims to determine the influence of service quality on purchasing decisions, the influence of promotion on purchasing decisions and the influence of service quality and promotion on purchasing decisions at Kula Kopi. This study uses two independent variables, namely service quality and promotion and one dependent variable, namely purchasing decisions. The data in this study were collected by distributing questionnaires to 138 consumers at Kula Kopi as research samples. The sampling technique used was purposive sampling. The data analysis method used was quantitative analysis, namely validity test, reliability test, classical assumption test consisting of normality test, multicollinearity test and heteroscedasticity test, multiple linear regression analysis, hypothesis test consisting of t-test and F-test. Based on data analysis, the results of the study indicate that the indicators in this study are valid and reliable. In the classical assumption test, the data is normally distributed, there is no heteroscedasticity and multicollinearity. In the hypothesis test in the t-test, it is known that the service quality variable has a significant effect on purchasing decisions, the promotion variable also has a significant effect on purchasing decisions. In the F test, it was found that service quality and promotion had a joint influence on purchasing decisions. Keywords: Service quality, promotion and purchasing decisions